Dry gangrene of lower limbs in a child: an adverse drug reaction to chloramphenicol - Samra, Tanvir; Chaudhary, Lalita; Kaur, Ranvinder (International Journal of Pharmacology and Toxicology, 2014)
Drug induced vasculitis is a potentially life and limb threatening complication which can be precipitated by intake of virtually any pharmaceutical agent. It is a diagnosis of exclusion as definitive diagnostic and laboratory criteria have not been defined. Withdrawal of the offending agent is the definitive therapy but use of antithrombotic, vasodilatory and anti-inflammatory agents has been proven to be beneficial. We report a case of dry gangrene of bilateral lower limbs and digits of the upper limb due to DIV secondary to the intake of chloramphenicol in a child diagnosed with typhoid fever. Keywords: Adverse Drug Reaction; Dry Gangrene; Chloramphenicol; Typhoid Fever; Drug Induced Vasculitis.